Perceived discrepancies in neurosonology training and certification across Europe: a RRFS/EAN survey - Tiu, Vlad; Durães, João; Di Lorenzo, Francesco; Vashchenko, Nina; Gonzalez-Martinez, Alicia; Accorroni, Alice; Carvalho, Vanessa; Sferruzza, Giacomo; Cuffaro, Luca (Frontiers in Neurology, 2024)
Introduction Neurosonology is a vital paraclinical investigation in modern neurology. However, access to education and certification in neurosonology for neurology residents and young specialists in Europe is challenging, and comprehensive data regarding this topic are scarce. Information regarding difficulties in neurosonology training across Europe may help bring this topic under the spotlight and act as a call for the harmonization of curricula across the continent. Methods We performed an online survey targeting European neurology residents and young specialists, focusing on neurosonology training and certification. The survey was conducted between May and September 2023 and received responses from 282 participants representing 37 European countries. Results There were disparities in neurosonology training during residency, with 6 (16.2%) out of 37 countries reporting a dedicated curriculum. The respondents expressed an overall lack of satisfaction with theoretical knowledge (rating their experience as very poor 28.0%, poor 20.2%, neutral 25.9%, good 19.3%, and very good 6.6%) and practical skills gained during their training (rating their experience as very poor 30.9%, poor 18.9%, neutral 22.6%, good 18.1%, and very good 9.5%). A total of 282 respondents (5.7%), 16 held a national certification in neurosonology, claiming obstacles such as high costs of certification and a limited number of certifying centers. Discussion This survey reveals significant variations in neurosonology training across Europe, indicating difficulties in obtaining certification. Despite the increasing importance of neurosonology, many neurologists feel inadequately prepared and lack practical training during residency, emphasizing the need for better and more standardized access. Conclusion The survey underscores challenges and disparities in neurosonology training and certification in Europe. Standardization of curricula and increased awareness about available certifications are crucial to address these issues. The interest in European Certification suggests a potential solution for enhancing neurosonology training at the international level.